2007
DOI: 10.1016/j.lwt.2006.05.011
|View full text |Cite
|
Sign up to set email alerts
|

Rancidity development in frozen pelagic fish: Influence of slurry ice as preliminary chilling treatment

Abstract: The slurry ice technology has shown profitable advantages when employed instead of traditional flake ice for the manufacture of chilled aquatic species. The present work is aimed at evaluating the effect of slurry ice as a preliminary treatment prior to frozen storage. For it, specimens of a small pelagic fatty fish species (sardine; Sardina pilchardus) were stored in slurry ice for 2, 5 and 9 days, then subjected to freezing (-80 1C; 24 h) and finally kept frozen (À20 1C) during 1, 2 and 4 months. At such tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
30
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 31 publications
6
30
0
1
Order By: Relevance
“…The results corroborate previous works describing remarkable rates of lipid hydrolysis mechanisms in different types of fish during frozen storage (Fazal and Srikar, 1989; Jong‐Ban et al., 1994;Fernandez‐Reiriz et al., 1995; Aubourg, 1999; Losada et al., 2005, 2006; Lugasi et al., 2007). In comparison to the mackerel, the shark contributed to more accelerated hydrolytic degradation of the fish lipids.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The results corroborate previous works describing remarkable rates of lipid hydrolysis mechanisms in different types of fish during frozen storage (Fazal and Srikar, 1989; Jong‐Ban et al., 1994;Fernandez‐Reiriz et al., 1995; Aubourg, 1999; Losada et al., 2005, 2006; Lugasi et al., 2007). In comparison to the mackerel, the shark contributed to more accelerated hydrolytic degradation of the fish lipids.…”
Section: Discussionsupporting
confidence: 91%
“…While the formation of FFA itself does not lead to nutritional losses, its assessment is deemed important when the effect of FFA on lipid matter has been proposed and explained on the basis of a catalytic effect of the carboxyl group on the hydroperoxide. Moreover, FFA being relatively small molecules, have been shown to undergo a faster oxidation rate than larger lipid classes of triglycerides and phospholipids, thus significantly affecting the sensory quality of aquatic food products (Losada et al., 2006; Morkore et al., 2007).…”
Section: Discussionmentioning
confidence: 99%
“…may be involved [25,33]. Freezing and thawing may also cause the lysis of mitochondria and lysosomes, events that may alter the distribution of enzymes and factors affecting the rate of enzyme reactions in tissues, so that deteriorative damage in frozen species could be accelerated [28,33]. According to the current results, previous SMB soaking proved to exert a favouring effect on secondary oxidation formation.…”
Section: Lipid Oxidation Assessmentmentioning
confidence: 80%
“…Tsighe et al () found 71.84% (w/w) in fresh sardines of the species Amblygaster sirm . Losada, Barros‐Velázquez, and Aubourg() evaluated Sardina pilchardus samples immersed in slurry ice with water solution and ice‐contained 3.3% sodium chloride. The authors observed similar moisture levels between in nature (71.8% w/w) and post‐treatment samples (70.5 to 73.5% w/w), demonstrating that, as in the present study, the storage conditions did not compromise the moisture levels of the fish.…”
Section: Resultsmentioning
confidence: 99%